2002
DOI: 10.1263/jbb.93.266
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Suppressive Monoclonal Antibody Belonging to the VH 7183 Family Directed to the Oncodevelopmental Carbohydrate Antigen on Human Hepatocellular Carcinoma

Abstract: Hep27 monoclonal antibody (Hep27 Mab) was raised by immunizing BALB/c mice with cells of the Thai human hepatocellular carcinoma (HCC) cell line HCC-S102 using hybridoma technology. The Hep27 Mab recognizes oncofetal development antigens by reacting with many HCC, other cancers, fetal and newborn liver but not adult liver. The Hep27 Mab alone markedly inhibits the growth of hepatocellular carcinoma cell lines (65% viability on the third day), suggesting its clinical usefulness. Moreover, complementary DNA (cDN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…In our previous study [1], we found that the viability of HCC-S102 cells was reduced to 85 %, 83 % and 65 % on the first, second, and third day, respectively, after treatment with 5 μg/ml of Hep27 Mab. No significant change could be found in negative control (HCC-S102 treated with Hep16 Mab, an Ab secreted from hybridoma clone without tumuricidal activity).…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…In our previous study [1], we found that the viability of HCC-S102 cells was reduced to 85 %, 83 % and 65 % on the first, second, and third day, respectively, after treatment with 5 μg/ml of Hep27 Mab. No significant change could be found in negative control (HCC-S102 treated with Hep16 Mab, an Ab secreted from hybridoma clone without tumuricidal activity).…”
Section: Resultsmentioning
confidence: 93%
“…Hep27 Mab showed no reactivity to normal liver and low binding activity to HCC-S102 treated with PDMP, an inhibitor of glycolipid synthesis. Furthermore, Hep27 Mab alone can inhibit tumor cell growth [1]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For this reason, research aimed at finding gene therapy vectors that could be targeted to HCC cells using specific monoclonal antibodies is being actively conducted[16]. Because monoclonal antibodies such as AF-20 [17] and Hep27 [18] bind to the antigen uniformly expressed in HCC-derived cell lines and human tumors, including those with distant metastasis, it is likely that they would have high specificity and efficiency as HCC-targeting gene transfer vectors. In addition, single-chain antibody fragments may have potential application for tumor targeting [19].…”
Section: Discussionmentioning
confidence: 99%